Relationships between Trait Emotional Intelligence, mood states, and future orientation among female Italian victims of Intimate Partner Violence. Issue 11 (November 2020) - Cabras, Cristina; Mondo, Marina; Diana, Angelica; Sechi, Cristina
Abstract: Objective: Trait Emotional Intelligence (EI) has been associated with psychological outcomes in many conditions; however, it has received little attention in the field of Intimate Partner Violence (IPV). We explored the relationship between trait EI, mood states, and future orientation in a sample of Italian women victims of IPV. Method: We recruited 409 help-seeking women who were victims of IPV. They completed the Trait Emotional Intelligence Questionnaire, Positive Affect-Negative Affect Schedule, Long-Term Personal Direction Scale, and Achievability of Future Goals Scale. Results: The results showed that trait EI was associated with the future orientation of IPV victims both directly and indirectly through the mood states. Conclusions: Our findings suggest potential paths for developing future psychoeducation methodologies designed at improving the quality of life of women IPV victims. Abstract : Psychology; Intimate partner violence; IPV; Women; Emotional intelligence; Trait EI; Mood states; Future orientation.